Repricing Avalanches - Nirei, Makoto; Scheinkman, José A. (Journal of Political Economy, 2024)
We present a menu-cost pricing model with a large but finite number n of firms. A firm’s nominal price increase lowers other firms’ relative prices, thereby inducing further nominal price increases. The distribution of these “repricing avalanches” converges as n→∞ to a mixture of generalized Poisson distributions with an indexofdispersion=1/(1−θ)2, where θ is determined by the equilibrium of the continuous limit. We calibrate the model to the US experience during 1988–2005 and obtain a θ surprisingly close to unity. Our model accounts for the positive relationship between inflation level and volatility observed in the data.